Nursing of a patient with hordeolum treated by ear-apex bloodletting therapy (1例麦粒肿患者耳尖放血的护理体会) - LI Shanshan (李珊珊); YANG Jianying (杨剑英) (Association of Integrative Nursing, 2023)
This paper reviewed the ear-apex bloodletting therapy and nursing management for a patient with hordeolum. According to the patient's evaluation results, the treatment problems were pointed out, and individualized Traditional Chinese Medicine treatment methods were formulated, including emotional management, dietary care, daily life management, drug care, etc. , Traditional Chinese Medicine by syndrome differentiation is aimed to to change the patient's condition, promote the recovery and improve the quality of life of the patient. (回顾性分析1例麦粒肿患者的临床资料, 总结耳尖放血的效果和相关护理措施。根据评估结果明确治疗和护理问题, 制定个体化中医治疗和护理方案, 在耳尖放血治疗的基础上, 实施情志护理、膳食护理、日常生活管理、药物护理等。通过中医辨证施护改善临床症状, 促进病情痊愈, 改善患者生活质量。)